Pengembangan Media Manipulatif tentang Materi Jaring-Jaring Kubus dan Balok untuk Siswa SD - Astuti, Widi; Karlimah, Karlimah; Apriani, Ika Fitri (Program Studi Pendidikan Matematika, 2024)
This study aims to develop manipulative media about cube and block nets for grade V elementary school students. This research uses research and development methods, namely R&D (Research and Development), ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study discusses the development of manipulative media, which is developed from manipulative media available in schools and manipulative media from previous studies. This development was validated by 2 expert validators, namely material experts and media experts. The development is adjusted to the latest curriculum, namely the independent curriculum and is also developed based on student characteristics. This is very important to do, because of the characteristics of grade V students, grade V students whose cognitive development is still at a concrete operational stage. Therefore they need concrete objects to understand something. Media quality is also very important to note, by paying attention to the quality of media in development, making media can be used repeatedly and not easily damaged. Then the display of media must also be considered in order to arouse students' enthusiasm. By developing this manipulative media, it can help students to understand the material, students' enthusiasm for learning increases, and the media becomes durable and can be used repeatedly. This development media can also help educators to explain learning material easily. Learning objectives are also achieved because this development media is also adjusted to the applicable curriculum.